Rethinking Arab democratization elections without democracy - Sadiki, Larbi (Oxford studies in democratization., 2009)
How do Arab countries democratise? This is the key question this book seeks to answer. To this end, the book assesses Arab democratic experiments and analyzes the opportunities and perils, highlighting the peculiarities of democratic transitions in the Arab Middle East.